Human-Animal Relationship: Understanding Animal Rights in the Islamic Ecological Paradigm - Islam, Nazrul (Journal for the study of religions and ideologies, 2015)
Animals have encountered cruelty and suffering throughout the ages. It is something perpetrated up till this day, particularly, in factory farms, animal laboratories, and even in the name of sports or amusement. However, since the second half of the twentieth century, there has been growing concerns for animal welfare and the protection of animal rights within the discourse of environmentalism, developed mainly in the West. Nevertheless, a recently developed Islamic Ecological Paradigm (IEP) rooted in the classical Islamic traditions contests the ‘Western’ monopoly of modern environmentalism, suggesting that there is much in Islamic traditions dealing with environmental issues including non-human animal species. IEP asserts that several centuries ago Islamic traditions significantly focused on and strongly advocated for animal welfare and animal rights. This paper explores and examines animal rights within the broader spectrum of Islamic environmentalism or Islamic eco-ethic. While the philosophical roots of IEP concerning animal rights date far back in seventh century, it can potentially make both ethical and educational contributions to the twenty-first century environmentalism and animal rights movements.